The value of PSA density in combination with PI-RADS™ for the accuracy of prostate cancer prediction - Distler, Florian A.; Radtke, Jan Philipp; Bonekamp, David; Kesch, Claudia; Schlemmer, Heinz-Peter; Wieczorek, Kathrin; Kirchner, Marietta; Pahernik, Sascha; Hohenfellner, Markus; Hadaschik, Boris (The journal of urology, 2017)
Purpose Multiparametric magnetic resonance imaging has an emerging role in prostate cancer diagnostics. In addition, clinical information is a reliable predictor of significant prostate cancer. We analyzed whether the negative predictive value of multiparametric magnetic resonance imaging to rule out significant prostate cancer could be improved using clinical factors, especially prostate specific antigen density. Materials and Methods. A total of 1,040 consecutive men with suspicion of prostate cancer underwent multiparametric magnetic resonance imaging first, followed by transperineal systematic and magnetic resonance imaging-transrectal ultrasound fusion guided biopsy. Logistic regression analyses were performed to test different clinical factors as predictors of significant prostate cancer and build nomograms. To simplify these nomograms for clinical use patients were stratified into 3 prostate specific antigen density groups, including group 1—less than 0.07, group 2—0.07 to 0.15 and group 3—greater than 0.15 ng/ml/ml. After stratification we calculated the negative predictive value of a PI-RADS (Prostate Imaging Reporting and Data System) Likert score of less than 3. Significant prostate cancer was defined as a Gleason score of 3 + 4 or greater. High grade prostate cancer was defined as a Gleason score of 4 + 3 or greater. Results Overall 451 men were diagnosed with significant prostate cancer, including 187 with a Gleason score of 4 + 3 or greater. On ROC curve analyses the predictive power of the developed nomogram for significant prostate cancer showed a higher AUC than that of PI-RADS alone (0.79 vs 0.75, p <0.001). The negative predictive value of harboring significant prostate cancer increased in men with unsuspicious magnetic resonance imaging from 79% up to 89% when prostate specific antigen density was 0.15 ng/ml/ml or less. In the repeat biopsy setting the negative predictive value of significant prostate cancer increased from 83% to 93%. The negative predictive value to harbor high grade prostate cancer increased from 92% up to 98% in the entire cohort. Conclusions Using prostate specific antigen density combined with multiparametric magnetic resonance imaging improved the negative predictive value of PI-RADS scoring. By increasing the probability of ruling out significant prostate cancer approximately 20% of unnecessary biopsies could be avoided safely.